Cytogenetic Markers Reinforce the Redescription of the Armored Pleco Hypostomus spiniger (Loricariidae - Hypostominae), an Endemic Species in the Uruguay River Basin and Patos Lagoon System - Takagui, Fabio Hiroshi (2023)
Among the Neotropical fish fauna, suckermouth armored catfishes (Hypostomus - Loricariidae) stands out as one of the most difficult groups to diagnose morphologically. So the use of different molecular markers, as is the case of cytogenetics, has been fundamental for a precise identification of some species. In the present study, we characterize the karyotypes of two allopatric Hypostomus spiniger populations, using classical and molecular cytogenetic methods. This species was described by Hensel (1870) but later synonymized with Hypostomus commersoni, and recently it was again recognized as a valid species. Taking to account this taxonomic problematic, the aim of this study is to determine chromosomal characters that may be useful to validate the taxonomic status of H. spiniger and to complement its diagnosis in relation to H. commersoni populations. The karyotype of H. spiniger is composed by 66 chromosomes (10m+16sm+14st+26a), few heterochromatin and a multiple nucleolar organizer regions (NORs) system. Despite, the currently geographic isolation among the samples collected in Forquetinha River (Patos Lagoon basin) and Quadros Lagoon (Tramandaí River basin), both shared the same karyotypic structure, this cytogenetic evidence, suggest that both populations belongs to the same species. Additionally, our results clearly distinguish H. spiniger from H. commersoni populations collected along the Paraná River basin, that exhibited 2n=68 chromosomes and several divergences in heterochromatin and NORs pattern. In sum, the present study reinforces the valid status of H. spiniger and demonstrated the importance of basic cytogenetic analysis to understand conflictuous taxonomic matters.